Gender-based leadership disparities: obstacles to women becoming leaders in student organizations - Raihannabil, Syfriza Davies; Novelia, Friska; Halma, Karini; Hastin, Nadya Noor; Rajagukguk, Marlon Brando (Privietlab, 2026)
This study identifies internal and external factors that hinder women from becoming leaders of student organizations. Traditional leadership stereotypes consider men to be more worthy of leadership than women, resulting in disparities in gender-based leadership. In fact, men and women should have equal opportunities to become leaders. This study simultaneously examines internal and external factors that hinder women from becoming leaders based on statistical and empirical evidence that has never been found in previous studies. The survey-based sampling study involved 90 respondents who were divided into female students who were and were not leaders of student organizations. The survey data were analyzed using binary logistic regression analysis. This study found that self-confidence and responsibility have a statistically significant effect on women's leadership. Women with lower self-confidence and responsibility show a lower tendency to become leaders. Understanding, knowledge, patriarchal culture, ability, and relationships did not show a significant effect. However, women who become leaders generally have higher knowledge, perceive less patriarchal culture, and have stronger relationships. The main obstacle for women in taking leadership positions is internal factors. Therefore, development programs that focus on increasing self-confidence and responsibility need to be a priority.